Adsorción de plomo mediante la utilización del exoesqueleto de camarón y cascarilla de arroz en aguas residuales de la industria fabricante de baterías - Pinargote Arauz, María Eugenia (2021)
The objective of the research was to determine the adsorption of lead by using the exoskeleton of shrimp (Litopenaeus vannamei) and rice husk (Oryza sativa) as filter substrates in wastewater from a battery manufacturing industry. For this, the completely random bifactorial design was used, consisting of four treatments with three repetitions, with 30% - 60% and 70% - 40% of shrimp exoskeleton and 70% - 40% and 30% - 60% of rice husk. Filtering a liter of residual water. Physicochemical analyzes were carried out such as: lead, electrical conductivity, turbidity, temperature and pH. The removal percentages resulting from the evaluated characterization parameters showed that the initial Pb content found in the wastewater of the battery manufacturing industry was 8.22 mg / l, this being higher than the maximum permissible limit established in Annex 1 of the Book VI of the unified text of Secondary Environmental Legislation (TULSMA), which establishes a maximum limit of 0.5 mg / l. The alternative hypothesis in this research was accepted, achieving 79.36% removal, simultaneously with the percentage proposed in the proposed hypothesis, where significance was emphasized in the T3 treatment with a higher amount of shrimp exoskeleton thanks to its physicochemical properties. The economic feasibility of the best treatment was studied using the production cost method; establishing a price of $ 25.35 without VAT which has a viable economic feasibility.